1992
DOI: 10.1084/jem.175.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Disparate interaction of peptide ligand with nascent versus mature class I major histocompatibility complex molecules: comparisons of peptide binding to alternative forms of Ld in cell lysates and the cell surface.

Abstract: SummaryTo determine the mechanism and structural consequences of peptide binding to class I molecules, we have studied the L d molecule of the mouse. Previous studies have shown that a significant proportion of surface and intracellular L a molecules can be detected in an alternative conformation designated Laalt, Ldalt molecules are non-ligand associated and show weak if any 32-microglobulin (32m) association. We report here that L a molecules have a relatively rapid surface turnover compared with other class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 41 publications
4
55
1
Order By: Relevance
“…TAP-proficient cells in general have more peptide-free MHC class I molecules at the cell surface than the TAP-deficient cells, even though the proportion of peptide-free molecules is larger in TAPdeficient cells (27). This is also true in our model, because staining of P815 cells with an Ab specific for peptide-free H-2L d (28,29) is brighter than that of RMA-S-L d (Fig. 4C).…”
Section: Alloreactive T Cells In Mtb Mice Are Peptide Dependentsupporting
confidence: 52%
“…TAP-proficient cells in general have more peptide-free MHC class I molecules at the cell surface than the TAP-deficient cells, even though the proportion of peptide-free molecules is larger in TAPdeficient cells (27). This is also true in our model, because staining of P815 cells with an Ab specific for peptide-free H-2L d (28,29) is brighter than that of RMA-S-L d (Fig. 4C).…”
Section: Alloreactive T Cells In Mtb Mice Are Peptide Dependentsupporting
confidence: 52%
“…Analysis of the chimeric D d -L d MHC class I molecule, D dm1 suggested that the amino-terminal half of L d (the ␣1 and ␣2 domains) was mostly responsible for its slow trafficking and assembly and weak ␤ 2 m association (2), in agreement with the structural studies cited above. Third, L d has a shorter half-life on the cell surface (3,10,11), and a higher proportion of the total L d molecules on the cell surface exists as open (mAb 64-3-7 ϩ ) forms (3,12). These latter findings suggest that peptide ligands associated with cell surface forms of L d tend to dissociate comparatively quickly to generate transient open forms of L d .…”
mentioning
confidence: 71%
“…This observation implies that the processing mechanism includes the exchange of stabilizing peptide for antigenic peptide derived from exogenous Ag. Peptide exchange is possible because components of the MHC-I complex (MHC-I heavy chain, ␤ 2 -microglobulin, and peptide) bind each other in a reversible and dynamic fashion (37,(45)(46)(47). It may seem paradoxical that the binding of high affinity peptides to MHC-I promotes a processing mechanism based on peptide exchange, but enhanced MHC-I survival conferred by stabilizing peptide enables MHC-I to survive for participation in processing, which apparently outweighs considerations of peptide competition.…”
Section: Discussionmentioning
confidence: 99%